Wasaith Ikhtibariyyah Qaimah Quizizz 'ala al-Tamayuz Fi Tahfiz Ta'allum al-Lughah al-'Arabiyyah - Hanifah, Umi; Muflihah, Muflihah (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2024)
The researcher conducted a study at MAN Sidoarjo, grade 10-4 with the aim of increasing students' motivation in learning the Arabic language, because many students have little or no interest in learning the Arabic language, which is considered the most difficult subject to comprehend. To increase this motivation, there is a need for appropriate means to increase this motivation, namely tests. This research utilizes the case study and literature study research methods, which use different elements of the same research at different times. The case study was applied by administering tests to students. The research was conducted by observing the students' condition when learning the Arabic language, i.e. students' motivation decreased to 48%, and with the use of Quizizz media students experienced an increase in students' learning motivation to an average of 73% with an increase in the category of students' learning motivation. The use of quiz media has a significant impact on students' learning motivation. Most of the students fall into the high motivation category, 73.3%. Compared to the low-motivated category of 26.6%. Therefore, it is highly recommended that teachers use Quizizzizz media as a means of learning Arabic.